Life history of the reindeer sinus worm, Linguatula arctica (Pentastomida), a prevalent parasite in reindeer calves - Haugerud, Rolf Egil; Nilssen, Arne C. (Rangifer, 1990)
Three hypotheses of life cycle have been tested. A direct transmission to reindeer hosts with monoxenous development is the most probable. Abundant parasites are generally thought to have much impact on host populations. When assessing potential damage in reindeer calves, it is essential to look at the total parasitic effect on infracommunity level.